1996
DOI: 10.1096/fasebj.10.11.8836045
|View full text |Cite
|
Sign up to set email alerts
|

PACAP modulates L‐type Ca 2+ channel currents in vascular smooth muscle cells: involvement of PKC and PKA

Abstract: The effect of pituitary adenylate cyclase activating polypeptide (PACAP) on the L-type Ca2+ channel current (L-channel current) was studied in smooth muscle cells prepared from the rat tail artery. PACAP caused an increase in the amplitude of the L-channel current. The maximal increase (56%) occurred at a PACAP concentration of 1 x 10(-8) M; higher concentrations resulted in a smaller increase. Investigation into the intracellular mechanisms of PACAP action revealed that the increase in L-channel currents was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 37 publications
(24 reference statements)
2
47
0
Order By: Relevance
“…This PACAP-mediated increase in intracellular Ca 2ϩ concentration occurs by influx of Ca 2ϩ through voltage-dependent Ca 2ϩ channels, including L-type Ca 2ϩ channels and/or by release of Ca 2ϩ from intracellular stores via a phospholipase C-␤ (PLC)-mediated pathway (42,49,(52)(53)(54). The data presented here delineate steps in the pathway involved in modulation of L-type Ca 2ϩ channels by PACAP and subsequent increase in Ca 2ϩ influx through these channels.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This PACAP-mediated increase in intracellular Ca 2ϩ concentration occurs by influx of Ca 2ϩ through voltage-dependent Ca 2ϩ channels, including L-type Ca 2ϩ channels and/or by release of Ca 2ϩ from intracellular stores via a phospholipase C-␤ (PLC)-mediated pathway (42,49,(52)(53)(54). The data presented here delineate steps in the pathway involved in modulation of L-type Ca 2ϩ channels by PACAP and subsequent increase in Ca 2ϩ influx through these channels.…”
Section: Discussionmentioning
confidence: 81%
“…Modulation of L-type Ca 2ϩ channels via cAMP-and PLC-mediated pathways raises some interesting questions, e.g. whether there is any cross-talk between the two modulatory pathways or whether the two pathways even converge at some point subsequent to the involvement of PKA and protein kinase C. Depending on the particular splice variant subtype of the PAC1 receptor involved, PACAP-38 can induce the activation of both AC and PLC (42,52). It will be interesting to see whether PACAP modulates L-type channels in Drosophila not only via a cAMPmediated pathway but also through the pathway involving PLC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in rabbit portal vein and rat mesenteric artery (Taguchi et al, 1997;Ruiz-Velasco et al, 1998) cAMP facilitates Ca 2 þ entry through L-type Ca 2 þ channels, and this is also the case for cardiac muscle (Kamp & Hell, 2000). On the other hand, in rat artery tail and guinea-pig detrusor smooth muscle (Chik et al, 1996;Kobayashi et al, 2003) cAMP exerts negative modulation. It has also been suggested that low concentrations of cAMP enhances Ca 2 þ currents via cAMP-dependent kinases, whereas higher concentrations of the nucleotide may inhibit Ca 2 þ currents through activation of PKG (Koh & Sanders, 1996;Ruiz-Velasco et al, 1998).…”
Section: S Morales Et Almentioning
confidence: 98%
“…A previous study (Erdling et al 2013 ) suggests that activation is via the stimulation of cAMP production in blood vessels, which modulates L-type calcium channels in vascular smooth muscle cells through the activation of both protein kinase A (PKA) and protein kinase C (PKC) mechanisms resulting in vasodilation (Chik et al 1996 ). PACAP also stimulates the release of the prostaglandin PGF in the wall of the arteries but does not affect other cyclooxygenase metabolites (Huang et al 1992 ;Kastner et al 1995 ).…”
Section: Pacap-induced Relaxations Of Basilar Arteriesmentioning
confidence: 99%